Parameterization of apparatus TELIT - Bílek, David; Břetislav, Skrbek (Manufacturing Technology Journal, 2010)
Nowadays every reliable activity simplification leading to time saving is an important positive. The constraint of customers to documentation of mechanical properties just on castings is everlasting. It can be achieved without submission of casting to destructive testing, by non-destructive structuroscopy. This contribution describes the possibility of non-destructive determination of ultimate tensile strength of castings of graphite cast irons using TELIT structuroscope and parametrization of mathematical model for non-destructively determined strength using this instrument.
Keywords: Structuroscopy; shape of graphite; strength; cast iron